2020
DOI: 10.1002/cssc.202001647
|View full text |Cite
|
Sign up to set email alerts
|

N‐Butylpyrrolidinone for Solid‐Phase Peptide Synthesis is Environmentally Friendlier and Synthetically Better than DMF

Abstract: Solid-phase peptide synthesis (SPPS) is the method of choice for the preparation of peptides in both laboratory scale and large production. Although the methodology has been improved during the last decades allowing the achievement of long peptides and challenging sequences in good yields and purities, the process was not revised from an environmental point of view. One of the main problems in this regard is the large amount of solvents used, and therefore the tons of generated waste. Moreover, the solvent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…In addition to DMF, three neat solvents and three binary solvent mixtures that have previously 22 been demonstrated to achieve good resin swelling and overall fast coupling reactions were initially included (Figure 2). Moreover, the neat solvent NBP, which has recently been promoted as a suitable alternative solvent for SPPS, 28,38,39 was included despite displaying a viscosity (3.3 mPa × s) well outside the range we have found acceptable (typically 0.5−1.1 mPa × s at room temperature). 22 Fmoc-Ala-Phe-Phe-Ala linked to the 2-chlorotrityl-PS resin was used as a model peptide for Fmoc-removal.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In addition to DMF, three neat solvents and three binary solvent mixtures that have previously 22 been demonstrated to achieve good resin swelling and overall fast coupling reactions were initially included (Figure 2). Moreover, the neat solvent NBP, which has recently been promoted as a suitable alternative solvent for SPPS, 28,38,39 was included despite displaying a viscosity (3.3 mPa × s) well outside the range we have found acceptable (typically 0.5−1.1 mPa × s at room temperature). 22 Fmoc-Ala-Phe-Phe-Ala linked to the 2-chlorotrityl-PS resin was used as a model peptide for Fmoc-removal.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…41 However, the polarity of the solvent is also believed to play a central role, and a recent report showed that aspartimide formation was reduced when switching from DMF to the less polar green solvent NBP. 42 To shed more light on this finding, we investigated aspartimide formation in binary solvent mixtures of different polarity. To this end, we synthesised scorpion toxin II (Fmoc-Val-Lys(Boc)-Asp(OtBu)-Gly-Tyr(tBu)-Ile) on a Wang-PS resin, a wellstudied model peptide that readily undergoes aspartimide formation.…”
Section: Aspartimide Formationmentioning
confidence: 99%
“…Maximum swelling was observed at 12 h at RT and at 3 h at 45°C. The polystyrene (PS) and ChemMatrix showed swelling values of (8,25,26) (Figure 2 and Table 3). We next tested the efficiency of PolarClean (also compared with DMF) for SPPS.…”
Section: Resultsmentioning
confidence: 99%